2023
DOI: 10.3390/nu15030596
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Nut Consumption on Blood Lipids and Lipoproteins: A Comprehensive Literature Update

Abstract: In the present review, we provide a comprehensive narrative overview of the current knowledge on the effects of total and specific types of nut consumption (excluding nut oil) on blood lipids and lipoproteins. We identified a total of 19 systematic reviews and meta-analyses of randomized controlled trials (RCTs) that were available in PubMed from the inception date to November 2022. A consistent beneficial effect of most nuts, namely total nuts and tree nuts, including walnuts, almonds, cashews, peanuts, and p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2023
2023
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 87 publications
0
3
0
1
Order By: Relevance
“…En general, el consumo de frutos secos puede disminuir el colesterol total (-0,09 a -0,28 mmol/L), colesterol LDL (-0,09 a -0,26 mmol/L) y triglicéridos (-0,05 a -0,17 mmol/L). Sin embargo, existe evidencia limitada sobre sus efectos sobre el colesterol HDL (36,37) .…”
Section: Dietas Basadas En Plantas Y Perfil Lipídico En Pacientes Con...unclassified
“…En general, el consumo de frutos secos puede disminuir el colesterol total (-0,09 a -0,28 mmol/L), colesterol LDL (-0,09 a -0,26 mmol/L) y triglicéridos (-0,05 a -0,17 mmol/L). Sin embargo, existe evidencia limitada sobre sus efectos sobre el colesterol HDL (36,37) .…”
Section: Dietas Basadas En Plantas Y Perfil Lipídico En Pacientes Con...unclassified
“…Earlier findings have elucidated that saturated and trans fatty acids tend to increase serum total cholesterol as well as LDL, while the HDL level decreases [ 191 ]. On the other hand, polyunsaturated fats boost the serum HDL level with a significant reduction in total cholesterol and serum LDL level [ 192 ]. In bakery products, substituting saturated fats up to 5% of energy with polyunsaturated fats rather than decreasing their quantity has a potential towards serum LDL reduction by 0.26 mmol/L [ 193 , 194 ].…”
Section: Citrus Peel-enriched Nutraceutical Productsmentioning
confidence: 99%
“…All nuts contain large amounts of lipids. Furthermore, both in vitro and in vivo studies have found nuts to possess a range of bioactive compounds with cardioprotective action (Figure 1) [5][6][7][8][9][10][11][12]. Hence, there is great interest in their use as food products for the prevention and treatment of cardiovascular diseases (CVDs) [1][2][3][4].…”
Section: Introductionmentioning
confidence: 99%